2011
DOI: 10.5402/2011/670358
|View full text |Cite
|
Sign up to set email alerts
|

No Prognostic Impact of p53 and P-Glycoprotein Expression in Patients with Diffuse Large B-Cell Lymphoma

Abstract: The aim of this study was to determine the clinical significances of p53 and p-glycoprotein (P-gp) expression on outcome predictors for patients with DLBC. We assessed the immunohistochemical expression of p53 and P-gp using formalin-fixed, paraffin-embedded specimens in 108 patients diagnosed with de novo DLBC. A high expression of p53 was found in 53.7% of the patients. No expression of P-gp was demonstrated in any of the specimens. There were no significant differences in the complete remission (CR) rate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In contrast, other studies assessing the prognostic signifi cance of P53 overexpression in DLBCL found no association with overall survival (14, 26). Present study, similarly to the Rujirojindakul et al (27), did not demonstrate statistical correlation between p53 expression and age, sex, LDH level, and B symptoms in patients with DLBCL. The fi ndings in our study suggest no relation between P53 expression and survival.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, other studies assessing the prognostic signifi cance of P53 overexpression in DLBCL found no association with overall survival (14, 26). Present study, similarly to the Rujirojindakul et al (27), did not demonstrate statistical correlation between p53 expression and age, sex, LDH level, and B symptoms in patients with DLBCL. The fi ndings in our study suggest no relation between P53 expression and survival.…”
Section: Discussionsupporting
confidence: 63%
“…Kramer et al showed that p53 expression was only related to a high tumor burden and was not an independent risk factor for survival in patients with DLBCL [6]. Similarly, in the present study, no significant correlation was found between p53 expression and OS or disease-free survival [5,10,23]. It has been found that p53 expression had no significant effect on OS.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies have reported that P53 expression is a poor prognostic factor in diffuse large B-cell lymphoma, 24,27 whereas others have shown no prognostic effect. [36][37][38] Multiple factors likely contribute to this inconsistency: different patient cohorts with variable clinical features; diverse biological features such as molecular subtypes; differences in treatment regimens used; and different P53 cutoff levels employed. The prevalence of P53 expression in this patient cohort was 33% using a cutoff of 50% positive cells, similar to that of other studies in the literature in which 20-50% of cases of diffuse large B-cell lymphoma were reported to be positive.…”
Section: Discussionmentioning
confidence: 99%